Respuesta :

Answer:

a= -1/9

b= -1/3

c= 0

Step-by-step explanation:

Answer:

a = 9, b = 3, c = 1

Step-by-step explanation:

Using the rules of exponents

[tex]a^{-m}[/tex] ⇔ [tex]\frac{1}{a^{m} }[/tex] ⇒ [tex]a^{m}[/tex] = [tex]\frac{1}{a^{-m} }[/tex] and [tex]a^{0}[/tex] = 1

Given

f(x) = [tex](\frac{1}{3}) ^{x}[/tex], then

f(- 2) =[tex](\frac{1}{3}) ^{-2}[/tex] = [tex]\frac{1}{3^{-2} }[/tex] = 3² = 9 ⇒ a = 9

f(- 1) = [tex](\frac{1}{3}) ^{-1}[/tex] = [tex]\frac{1}{3^{-1} }[/tex] = [tex]3^{1}[/tex] = 3 ⇒ b = 3

f(0) = [tex](\frac{1}{3}) ^{0}[/tex] = 1

ACCESS MORE